Integrasi Computational Thinking dalam Pembelajaran Matematika di Madrasah Ibtidaiyah - Safik, Moh. (IBTIDA', 2022)
This research aims to investigate the relevance and stages of integrating Computational Thinking in mathematics learning at Madrasah Ibtidaiyah (Islamic primary schools). The approach used is qualitative-descriptive. The research findings indicate that Computational Thinking in mathematics learning has significant relevance in developing critical thinking skills, and problem-solving abilities, and preparing students to face challenges in the digital era. Computational thinking helps students connect mathematical concepts to real-world contexts, motivates learning, and establishes a relationship between mathematics and everyday life. Meanwhile, the integration of Computational Thinking in mathematics learning at Islamic primary schools requires a holistic and sustainable approach to ensure effective understanding and implementation.